1998
DOI: 10.1001/archsurg.133.2.149
|View full text |Cite
|
Sign up to set email alerts
|

A Preoperative Biliary Stent Is Associated With Increased Complications After Pancreatoduodenectomy

Abstract: Background: A preoperative biliary stent is commonly used after the initial evaluation of the patient with a periampullary mass. Objective: To evaluate the effect of a preoperative biliary stent on operative difficulty, postoperative complications, and length of hospital stay after a pancreatoduodenectomy. Design: A retrospective review of a prospectively collected consecutive series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(71 citation statements)
references
References 10 publications
2
66
1
2
Order By: Relevance
“…First, the significant effect of losartan in lowering both the wedged hepatic venous pressure, a direct measurement of the actual sinusoidal pressure, as well as the HVPG, the sinusoidal pressure corrected for the hepatic vein pressure. Second, the classic clinical example of sinusoidal portal hypertension is alcoholic cirrhosis, which has a reversible resistance component (10); and in the present and previous studies, losartan had the greatest effect in the patients with alcoholic cirrhosis (1,2,4). Losartan also has a diuretic and natriuretic effect (11).…”
Section: Does Losartan Work After All?mentioning
confidence: 53%
See 1 more Smart Citation
“…First, the significant effect of losartan in lowering both the wedged hepatic venous pressure, a direct measurement of the actual sinusoidal pressure, as well as the HVPG, the sinusoidal pressure corrected for the hepatic vein pressure. Second, the classic clinical example of sinusoidal portal hypertension is alcoholic cirrhosis, which has a reversible resistance component (10); and in the present and previous studies, losartan had the greatest effect in the patients with alcoholic cirrhosis (1,2,4). Losartan also has a diuretic and natriuretic effect (11).…”
Section: Does Losartan Work After All?mentioning
confidence: 53%
“…In direct contrast, the next randomized study, by Gonzalez-Abraldes et al (3), comparing 50 mg of losartan to propranolol for 6 wk, found that losartan had absolutely no effect in lowering HVPG (Ϫ2%), but significantly decreased MAP by 8%, whereas propranolol caused a significant, expected reduction in HVPG of 10%. The third study, by Schepke et al (4), using another angiotensin II receptor antagonist, irbesartan, 150 mg daily for 1 wk at a dose equivalent to 25 mg of losartan, significantly reduced HVPG by 12% compared to placebo, and lowered MAP by 5%. However, in patients with significantly elevated plasma renin activity (Ͼ900 U/ml), arterial hypotension was severe enough to cause renal impairment in these patients and their withdrawal from the trial.…”
Section: Does Losartan Work After All?mentioning
confidence: 99%
“…Several retrospective studies and prospective randomized trail have failed to demonstrate the benefit of PBD on postoperative outcomes after pancreaticoduodenectomy in jaundiced patients with pancreatic head cancer [3][4][5][6][13][14][15][16][17][18][19][20]. However some meta-analysis and reviews have shown that this strategy was associated with higher rate of postoperative complications [12,13,[19][20][21][22][23].…”
Section: Discusionmentioning
confidence: 99%
“…Numerous randomized controlled trials have addressed the issue of preoperative biliary drainage and its impact on perioperative and postoperative results [3,4]. However, reports on outcomes of pancreatoduodenectomy following PBD have been conflicting.…”
mentioning
confidence: 99%
“…The Memorial Sloan Kettering Group has reported that pre-operative biliary drainage is associated with a 4-fold increase in septic morbidity in the postoperative period and a significantly increased mortality. [39][40][41][42] However, there are large volume centres who have data to support the contention that pre-operative drainage is not necessarily a bad thing (Table 4). [45][46][47] Sohn et al 44 reviewed 567 patients who had been subjected to pancreaticoduodenectomy.…”
Section: The Clinical Datamentioning
confidence: 99%